2009
DOI: 10.1007/s00425-009-1039-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, functional analysis and localization of a novel gene encoding polygalacturonase-inhibiting protein in Chorispora bungeana

Abstract: Polygalacturonase-inhibiting proteins (PGIPs) are plant defense proteins. To date, no spatial distribution of PGIPs and interaction between PGIPs and nitric oxide (NO) in plant were described. Here, we first reported the full-length cDNA sequence of PGIP of Chorispora bungeana (CbPGIP1). Notably, immunofluorescence localization showed that the CbPGIP was evenly distributed in leaves but it was mainly localized in epidermis and vascular bundle in stems and roots. Further studies indicated that CbPGIP had higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Transcriptome profiling and molecular genetics have analyzed the stress regulatory network of C . bungeana , a subnival alpine plant with inherited cold tolerance [ 33 37 , 39 , 40 ], but little is known about the direct effects of low temperature on epigenetic regulation. Using a combination of the MS-AFLP technique and integrated statistical analyses, we found an interesting variation in DNA methylation of C .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcriptome profiling and molecular genetics have analyzed the stress regulatory network of C . bungeana , a subnival alpine plant with inherited cold tolerance [ 33 37 , 39 , 40 ], but little is known about the direct effects of low temperature on epigenetic regulation. Using a combination of the MS-AFLP technique and integrated statistical analyses, we found an interesting variation in DNA methylation of C .…”
Section: Discussionmentioning
confidence: 99%
“…The gene-specific primers for real-time PCR analysis were designed using the www.idtdna.com/Primerquest and Primer Premier (version 5.0) software (PREMIER Biosoft). The primer pairs that were used were CBT10872 ( and ), CBT28565 ( and ), CBT12464 ( and ), CbADH1 (CBT4440) ( and ), CbUGT (CBT18111) ( and ), and CbPGIP (EU441203) [ 33 ] ( and ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Chorispora bungeana, immunolocalization of defense-related proteins in leaves, stems and roots have shown copious fluorescence in leaves, mainly localized in epidermis, and recorded high in vascular bundles of stems and roots. The fluorescence signal of the control was nearly absent in stem, but not in leaf and root [37]. In Phaseolus vulgaris, during compatible interactions, no significant accumulation of defense-related protein was observed in hypocotyls and a very weak accumulation seen in leaves during lesion formation in Phaseolus vulgaris [38].…”
Section: Discussionmentioning
confidence: 87%
“…In our previous study, we reported CbPGIP1 was induced by S. solani infection (Di et al, 2009). In order to test individual AtPGIP gene expression mediated by S. solani infection, we performed qRT-PCR to assay AtPGIP1 and AtPGIP2 expression in Arabidopsis under disease stress.…”
Section: Discussionmentioning
confidence: 99%